Geneviève Castrée's Unmade Beds: Graphic Memoir and Digital Afterlives. Issue 1 (18th September 2018) - Rifkind, Candida
This article draws on comics studies, autobiography theory, and feminist theory to explore two autographics by the late Québecoise cartoonist Geneviève Castrée (1981–2016) and their mobilization online by a bereaved comics community. The article begins with Castrée's Susceptible (2012 ), a graphic memoir of coming-of-age in a dysfunctional family in 1980s Québec. By focusing on lettering, layouts, and the braided motif of the bed, I show that Castrée draws her maternal home as a conflicted space of both anxiety and security. This analysis extends toCastrée's 2015 series of self-portraits, 'Blankets Are Always Sleeping, ' in order to reflect on the complex figure of the Sad Girl as a sign of gendered resistance. After her untimely death, images of the sleeping cartoonist were mobilized on social media by bereaved fans. I argue that this digital circulation inevitably simplified and sentimentalized her autographic persona, as the remediation of her self-portraits online transferred their signification from individual expression to communal grief. The article concludes with two graphic elegies posted online by Diane Obomsawin and Vanessa Davis in the week after Castrée's death to consider her posthumous place amongst North American female cartoonists.